Reply to: Comment on: Serum Cholesterol and Incident Alzheimer's Disease: Findings From the Adult Changes in Thought Study. Issue 6 (20th March 2019) - Marcum, Zachary A.; Walker, Rod; Bobb, Jennifer F.; Sin, Mo‐Kyung; Gray, Shelly L.; Bowen, James D.; McCormick, Wayne; McCurry, Susan M.; Crane, Paul K.; Larson, Eric B.
Abstract : This letter comments on the letter byNaharci et al .